Registration of 'Cameo' soft white winter club wheat. Issue 3 (26th August 2022) - Garland‐Campbell, Kimberly; Bellinger, Brian S.; Carter, Arron H.; Chen, Xianming; DeMacon, Patricia; Engle, Doug; Hagerty, Christina H.; Kiszonas, Alecia; Klarquist, Emily; Murray, Timothy; Morris, Craig; Neely, Clark; et al.
Abstract: Soft white club winter wheat ( Triticum aestivum L. ssp. compactum ) is an important component of soft white wheat production in the Pacific Northwest of the United States. Most of the current club wheat production is in the <350 mm annual precipitation zone in central Washington, but there is interest in club wheat in the Palouse region of the United States (the counties of Whitman and Garfield in Washington and in Latah County in Idaho). Growers are continuing to grow the older club wheat cultivars 'Cara' and 'Coda', and there is a need for a new winter club wheat targeted to this region. 'Cameo' club wheat (Reg. no. CV‐1192, PI 699960), tested as ARS09X492‐6CBW, with awned spikes and soft white kernels, was developed using the bulk‐pedigree breeding method from the cross ARSC96059‐2/IL01‐11934//ARSC96059‐2‐0‐16. Cameo has better agronomic performance than other club wheat cultivars in trials on the Palouse, better stripe rust resistance than the club wheat 'ARS Crescent', tolerance to several major biotic and abiotic stressors, consistent good grain volume weight, mid‐season maturity and moderate height, excellent club wheat quality, and tolerance to low falling numbers. Cameo is not as competitive for grain yield in the traditional club wheat growing area in central Washington but is well suited to increasing the acreage of club wheat in the Palouse region of Idaho and Washington. Core Ideas: Club wheat is a high‐value component of the soft white wheat crop. Cameo club wheat will improve the end use quality of the soft white wheat crop. Cameo club wheat possesses resistance to multiple biotic and abiotic stressors. Cameo is best adapted to northeastern Oregon, northern Idaho, and eastern Washington. Cameo was developed from a diverse pedigree that includes club, soft white, and soft red winter wheat.